DEVELOPMENT OF A MICROCONTROLLER BASED ROBOT AND ITS USE IN TEACHING CONTROL AND NAVIGATION - Samuel Oliver Wane; Matthew Butler; Anthony James Bautista (Proceedings on Engineering Sciences)
This paper sets out a framework for the essential elements necessary for the implementation of outdoor autonomous mobile robots along with example algorithms. Robotics is a multi-disciplinary subject requiring a hands-on approach when developing machines to interact in the real world. Courses in robotics exist which either include simulated robots, access to robots in a laboratory, or remote access to robots in a controlled indoor environment. This study presents a teaching system based on a robust robot with a focus on navigation and communications in an uncontrolled outdoor agricultural environment. An all-terrain robot teaching platform was developed with the necessary hardware, libraries, and teaching material consisting of lectures and practical field-work. The course is tested on a variety of student levels and understanding is assessed with practical demonstration. This article shares the teaching philosophy and an overview of the hardware and software.